The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1116/1.588820
|View full text |Cite
|
Sign up to set email alerts
|

High selectivity plasma etching of silicon dioxide with a dual frequency 27/2 MHz capacitive radio frequency discharge

Abstract: Articles you may be interested inInfinitely high etch selectivity during CH 2 F 2 / H 2 dual-frequency capacitively coupled plasma etching of silicon nitride to chemical vapor-deposited a -C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 5 publications
2
40
0
Order By: Relevance
“…[9][10][11] Our group has investigated the driving frequency effects in atmospheric pressure CCP, including a dual frequency study. 12,13 The dual frequency experiment is still in progress, but it has been found that the addition of 2 MHz power enlarged the abnormal glow regime for 13.56 MHz plasma by lowering the required power for the plasma to fill the entire electrode area.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Our group has investigated the driving frequency effects in atmospheric pressure CCP, including a dual frequency study. 12,13 The dual frequency experiment is still in progress, but it has been found that the addition of 2 MHz power enlarged the abnormal glow regime for 13.56 MHz plasma by lowering the required power for the plasma to fill the entire electrode area.…”
Section: Introductionmentioning
confidence: 99%
“…The C 4 F 8 /CH 2 F 2 /O 2 /Ar and C 4 F 6 /CH 2 F 2 /O 2 /Ar mixture gas chemistries have been typically used for SiO 2 contact etching, but no detailed experimental works on the DFS-CCP etching system have been reported [3,6,8,16,18,22,31,36]. In this study, we compared the silicon dioxide etching characteristics using C 4 F 8 and C 4 F 6 based plasmas in a DFS-CCP etching system under different frequency combinations (f HF /f LF ) while varying the process parameters, such as the dc self-bias voltage (V dc ), O 2 flow, and the CH 2 F 2 flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] High-frequency ͑HF͒ power source controls plasma generation, i.e., the fluxes and species of the ions and radicals and low-frequency ͑LF͒ power source controls the dynamics of ions in the sheath where the degree of ion acceleration, i.e., ion energy is controlled. The LF and HF sources are coupled to two separate electrodes [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] in the conventional 2f-CCP etchers but recently both power sources to the one electrode in dual frequency superimposed CCP ͑DFS-CCP͒ etchers. [1][2][3][4][5][7][8][9][10][11][12][13][14] Two main characteristics of some commercial 2f-CCP etchers are the use of very-high frequency ͑VHF͒ sources larger than 27.12 MHz for high density plasma generation as well as superimposition of the two LF and HF power sources for the simplicity in the system design.…”
Section: Introductionmentioning
confidence: 99%